Low-dose trimethoprim-sulfamethoxazole for prophylaxis of Pneumocystis jirovecii pneumonia in HIV-uninfected patients: a systematic review and meta-analysis - Huang, Hui-Bin; Shi, Jia-Heng; Hu, Yan-Ge; Zhu, Yi-Bing; Yu, Da-Xing (Frontiers in Pharmacology, 2025)
BackgroundTrimethoprim-sulfamethoxazole (TMP-SMX) is the recommended first-line prophylactic agent against Pneumocystis jirovecii pneumonia (PJP). However, the standard regimen is often discontinued due to its drug-associated adverse events (AEs), especially in immunocompromised patients without HIV infection. Therefore, we aimed to investigate the efficacy and safety of a low-dose regimen of TMP-SMX against PJP prophylaxis in patients without infection.MethodsWe searched PubMed, Embase, Wanfang, China National Knowledge Infrastructure, Web of Science, and the Cochrane database for relevant articles from inception to 15 October 2024. Studies were included if they reported the safety and efficacy of using TMP-SMX in PJP prophylaxis in patients without HIV infection. The primary outcome was the discontinuation rate. We assessed study quality and performed sensitivity and subgroup analysis to explore potential heterogeneity among the included studies.ResultsSeventeen studies with 4,890 patients were included. These studies were low to modest in quality. Overall, the incidence of PJP in the included studies was rare and was similar between the low- and standard-dose groups. However, the low-dose regimen significantly reduced the risk of discontinuation rate (odds ratio [OR] = 0.38; 95% CI, 0.27–0.52; I2 = 0%; P < 0.00001). Further sensitivity and subgroup analyses confirmed this finding. Estimation of the combined discontinuation rate for patients receiving low-dose TMP-SMX was 10% (95% CI, 4%–16%). The low-dose regimen also significantly reduced total AEs (OR = 0.33; 95% CI, 0.24–0.46; I2 = 22%; P < 0.00001) and improved the incidence of most specific AEs (ORs ranged from 0.24 to 0.67), especially in outcomes of fever, rash, thrombocytopenia, hyponatremia, and liver and renal function (P values ranged from 0.0001 to 0.02).ConclusionOur findings suggested that a low-dose TMP-SMX regimen is safe and significantly reduces the discontinuation rate and total AEs compared to the standard regimen against PJP in HIV-uninfected patients. Thus, it is a potentially promising prophylactic regimen, and more well-designed, high-quality research should be conducted.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-4-0084/.